Assessment of Colon Cancer Screening Programs in Sulaimaniyah Province, Iraq - Abdulrazaq, Sivar Tahir; Sheikha, Anwar Kader Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The incidence and mortality of colorectal cancer (CRC) have increased over the last 25 years in young adults aged <50 years old. Early diagnosis, particularly through screening programs, is one of the major factors contributing to this welcome development. Objectives: To assess the knowledge of the CRC screening program among people in the Sulaimaniyah province, Iraq, about their sociodemographics and levels of knowledge. Patients and Methods: A descriptive cross-sectional study was conducted on 300 participants through an online questionnaire and interview. The collected data includes participants' sociodemographic data (age, gender, level of education, marital status, and occupation) and their knowledge of the CRC screening program. Results: The mean age of participants was 50.5±5.8 years, ranging from 30 to >70 years. Most participants were males (51%), married (61.8%), governmental employees (58.7%), and graduated from university (28.7%). More participants (77.6%) had an acceptable level of knowledge related to the CRC screening program, 17.7% had a good level, and only 4.7% had a poor level. Knowledge of the CRC screening program was statistically significant with age, occupation and marital status (p=0.02, p<0.01, and p<0.01, respectively). Conclusions: The outcomes showed most participants had fair knowledge regarding the CRC screening program. Nurses must have a good role and play an important part in health education about CRC. Thus, early detection programs, regular screening, and lifestyle maintenance decrease the risk of CRC in the community.
Keywords: Assessment; knowledge; colon cancer; screening program; nurse role